An All LTPS-TFT-Based Charge-Integrating Amplifier for Sensor-Array Readout Circuit on Flexible Substrate - Mohit Dandekar; Kris Myny; Wim Dehaene (IEEE Open Journal of the Solid-State Circuits Society, 2022)
This article presents the design of a readout circuit for charge-output sensor arrays integrated on a flexible substrate. The charge-integrating amplifier is built with a current-output transimpedance amplifier that includes the integrator function with reset. The charge-integrating amplifier has a fully differential internal topology, improving over single-ended design, including the feedback amplifier implemented specifically as a Nauta-transconductor. The readout circuit has been manufactured in a 3- $μ \text{m}$ low-temperature polysilicon process on foil and measured, achieving a bandwidth of 200 kHz, operation at a 5-V supply while consuming 586- $μ \text{W}$ power and maintaining a maximum integral nonlinearity of 5%.